A nontranscriptional role for Oct4 in the regulation of mitotic entry - Zhao, Rui (Proc Natl Acad Sci U S A, 2014)
Rapid progression through the cell cycle and a very short G1 phase are defining characteristics of embryonic stem cells. This distinct cell cycle is driven by a positive feedback loop involving Rb inactivation and reduced oscillations of cyclins and cyclin-dependent kinase (Cdk) activity. In this setting, we inquired how ES cells avoid the potentially deleterious consequences of premature mitotic entry. We found that the pluripotency transcription factor Oct4 (octamer-binding transcription factor 4) plays an unappreciated role in the ES cell cycle by forming a complex with cyclin–Cdk1 and inhibiting Cdk1 activation. Ectopic expression of Oct4 or a mutant lacking transcriptional activity recapitulated delayed mitotic entry in HeLa cells. Reduction of Oct4 levels in ES cells accelerated G2 progression, which led to increased chromosomal missegregation and apoptosis. Our data demonstrate an unexpected nontranscriptional function of Oct4 in the regulation of mitotic entry.